ARDUINO-BASED DEVICE MODELING: INDOOR AIR QUALITY OF SICT THE RESULTS OF EVALUATION STUDIES - Nomin-Erdene Т.; Одончимег, Лхагва (Перспективные направления инновационного развития и подготовки кадров, 2024)
As the level of air pollution increases, it starts to damage our environment. But whenever the topic of air pollution comes up, we talk about the environment. Outdoor air pollution also affects indoor air. In our research, we measured indoor air pollution in University using Arduino boards, gas, humidity, and temperature sensors. In this work, we proposed a cheap air quality monitoring system based on Arduino uno microcontroller. The Arduino is connected to 2 sensors and the measured data is displayed on the LCD screen. The sensors used are DHT11 for humidity and temperature sensors and Mq-2 for carbon dioxide (CO2). Our device is a device capable of taking measurements of real-time conditions. Air pollution in the school environment was measured with this simulated device and the results were obtained.